2019
DOI: 10.1155/2019/6793957
|View full text |Cite
|
Sign up to set email alerts
|

Prooxidative Activity of Celastrol Induces Apoptosis, DNA Damage, and Cell Cycle Arrest in Drug-Resistant Human Colon Cancer Cells

Abstract: Cancer resistance to chemotherapy is closely related to tumor heterogeneity, i.e., the existence of distinct subpopulations of cancer cells in a tumor mass. An important role is assigned to cancer stem cells (CSCs), a small subset of cancer cells with high tumorigenic potential and capacity of self-renewal and differentiation. These properties of CSCs are sustained by the ability of those cells to maintain a low intracellular reactive oxygen species (ROS) levels, via upregulation of ROS scavenging systems. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 40 publications
3
36
0
Order By: Relevance
“…Plant extracts and/or the thereby-derived phytochemicals are known to provoke cancer cell death by causing oxidative damage to genetic material-mediated cell cycle arrest and subsequent cell death [ 59 , 60 ]. With this in mind, the DNA damage to HepG2 cellular DNA following T. bentzoë crude extract treatment was investigated using the alkaline comet assay, and scored in terms of tail length, tail intensity and olive tail moment.…”
Section: Discussionmentioning
confidence: 99%
“…Plant extracts and/or the thereby-derived phytochemicals are known to provoke cancer cell death by causing oxidative damage to genetic material-mediated cell cycle arrest and subsequent cell death [ 59 , 60 ]. With this in mind, the DNA damage to HepG2 cellular DNA following T. bentzoë crude extract treatment was investigated using the alkaline comet assay, and scored in terms of tail length, tail intensity and olive tail moment.…”
Section: Discussionmentioning
confidence: 99%
“…Plant extracts and/or thereby derived phytochemicals are known to provoke cancer cell death by causing oxidative damage to genetic material mediated cell cycle arrest and subsequent cell death [50,51]. With this in mind, the DNA damage to HepG2 cellular DNA following T. bentzoë crude extracts treatment was investigated using the alkaline comet assay and scored in terms of tail length, tail intensity, and olive tail moment.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous papers, the level of intracellular ROS between drug-resistant cells and their sensitive counterparts differs significantly. Moreira et al [21] demonstrated that the LoVo/DX cell line displayed a significantly lower level of intracellular ROS than the drug-sensitive line LoVo. Maiti had similar results comparing ovarian cancer cell lines [22].…”
Section: Biological Evaluationmentioning
confidence: 99%
“…ROS-induced DNA damage is a well-known mechanism of action of many cytostatics [23]. Elevating the ROS level over a certain level may be an important factor in tumor chemotherapy since the initial level of intracellular ROS level for LoVo/DX is lower than for LoVo [21,22]. Rh-123 accumulation was observed in all examined compounds regardless of the used concentration, except compound 3, where accumulation was observed only for concentrations in the range of 10-20 µ M (Figure 3).…”
Section: Biological Evaluationmentioning
confidence: 99%
See 1 more Smart Citation